Assessing the necessities in pharmaceutical care of immigrants in Campo de Gibraltar. - Vazquez V; Espejo J; Faus MJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Some specific barriers impede the normal integration of the immigrant in the healthcare system, and those barriers are augmented in non-legal immigrants. Pharmacists can contribute in improving immigrants' healthcare and pharmaceutical care. Objective: To analyze pharmaceutical care received and drug accessibility of non-legal immigrants in the area of Campo de Gibraltar. Methods: We carried out personal interviews to immigrants. Questionnaires translated into three languages (Arabian English and French) were validated (translation retro-translation) and used. Two translators interviewed the immigrants in one of those languages, the one chosen by the interviewed patient. Results: Immigrants present negative clinical outcomes associated with their medication and economic difficulties to acquire their medicines. To improve pharmaceutical care they are receiving, they demand more information on their illnesses, the use of their medicines, and bigger accessibility to them. Conclusions: Immigrants were not worried about health care or pharmaceutical care, because they have other major worries produced by their legal status. Nevertheless, they constitute a group with higher risk of presenting negative clinical outcomes of medication. Medicines' expenditure constitutes a barrier to the healthcare process, reduced by NGOs.